KnowledgeManagementSystems - Ronald Maier (2007)
The transformation of organizations into knowledge-intensive and knowledgeaware organizations takes place at an ever-increasing pace. Knowledge as the key resource, not labor, raw material or capital, changes production functions in organizations significantly. Knowledge represents the key concept to explain the increasing velocity of the transformation of social life in general and the way businesses and social institutions work in particular (Drucker 1994). Estimates at leading research organizations suggest that up to 60% of the gross national product in the United States is based on information as opposed to physical goods and services (Delphi 1997, 10). In the last decade, this percentage is likely to have further increased which is reflected by a large number of studies that report similar or higher values. The big share is not surprising as it is estimated that the knowledgeintensive construction and development process of new products and services potentially determines 80 to 90% of the resulting production costs (Scherrer 1999, 131).